Costing analysis of Alam Mimpi Sendirian Berhad / Usun Stewart Ngau ... [et al.] - Ngau, Usun Stewart; Maria, Lukas @ Lucas; Salem, Stephen Buding; Atin, Paul Kundang; Nyandot, Moed; Abdullah, Malvern (2004)
This report is a detailed costing analysis on the production and costing processes of Alam Mimpi Sendirian Berhad (AMSB). This company has been producing polyurethane mattresses, pillows and cushions for sale. The management finds that their prices are not competitive enough in the market and has attributed their high prices to their high costs. The company’s current production processes and costing scenario will be analysed using the activity based costing (ABC) method. From the analysis, the group will make suggestions and recommendations for the company to consider lowering their costs and improving their competitiveness in the market. Chapter one explains the background and purpose of this study as well as the overview of the company. This chapter also includes the problem statement, objectives, and scopes and limitations of the study. Chapter two discusses the literature review on the history of mattress and the polyurethane industry, and the concept of the costing method used to analyse the data. Chapter three explains the methodology used to obtain the relevant data and discusses the various steps on how the data are analysed. The analysis and findings are presented in chapter four where it is found that there are great cost differences between the costing method currently used by the company and the ABC method. Chapter five discusses the conclusion and recommendations where it is concluded and recommended that the ABC method is more appropriate in allocating overheads for the company’s products.